IMPROVEMENT OF TAXATION TO STRENGTHEN THE FINANCIAL STABILITY OF ENTERPRISES - KHOMENKO, Lyudmila (Herald of Khmelnytskyi National University. Economic sciences, 2024)
One of the leading tax incentives that the state can provide to industrial enterprises in difficult times to improve their business efficiency is a full or partial waiver of profit taxation, namely a portion of tax revenues to the budget. At the same time, the provision of even targeted tax incentives sets a precedent for their effective use. The process of reproduction to stabilize the equilibrium of the current stage requires a transition to a new level of economic relations, including the use of the tax regulation mechanism. Approaches to the use of the tax regulation mechanism are outlined in relation to: investment tax credit, as from the timing of tax payments in the part of expenses from profit on innovation; tax holidays for the payment of tax on income obtained from the implementation of innovative projects within the term of several years; reduction of the tax on the growth of innovation expenses; preferential taxation of profit obtained through the use of intellectual property. The necessity to track the usage of the received benefits in the form of a tax credit for the innovative development of industrial production in the conditions of accelerated implementation of the achievements of scientific and technical progress is justified. A conclusion was made regarding the provision of tax benefits for innovative investment projects based on compliance with established special criteria regarding investment volumes, their compliance with priority areas of investment activity and expected socio-economic results. In order to provide such a benefit, a reasonable step is to keep a separate record of the results of the implementation of the investment project and related expenses. A special adjustment of the value of assets for compensation of the underestimation of real depreciation in inflationary conditions in case of introduction of innovations is detailed. Using Tereshchenko’s model, the probability of bankruptcy of an investment-innovative steel factory was calculated. It is proposed to create an anti-crisis headquarters consisting of a group of specialists in the main areas, including a financial specialist for substantiating calculations for obtaining a tax credit for future innovative improvements.